PENERAPAN MODEL PEMBELAJARAN SAVI BERBANTUAN GOOGLE ART DAN CULTURE UNTUK MENINGKATKAN HASIL BELAJAR SBDP DI SD - Muhlis, Muhlis; Asteriani, Devi; Buhari, Muh. Ramli; Mustamiroh, Mustamiroh; Wahyuningsih, Tri (JS (JURNAL SEKOLAH), 2023)
Abstract: The aim of the research is to improve learning outcomes using the application of learning models Somatic Auditory Visual Intellectual (SAVI) assistedGoogle Art and Culture SBdP lesson material on various regional fine arts for class V SD Negeri 002 Loa Kulu for the 2022/2023 academic year. This type of Classroom Action Research (CAR) was carried out over two cycles consisting of four meetings. The research procedure consists of four stages, namely planning, implementation, observation and reflection. The research subjects were 28 class V students and the research objects were the results of SBdP learning about various regional fine arts materials using the SAVI learning model. Data collection techniques used were observation, tests and documentation. Research data analysis techniques use percentages of teacher and student activity, completeness of learning outcomes, averages, final grades and increases in student learning outcomes. The results of the research showed that the average SBdP score for students in the pre-cycle was 52.5 with a percentage of students completing at 32.14% with a total of 9 students completing, then in the first cycle the average score increased to 66.96 with an increase in the percentage of learning outcomes. amounted to 27.54% and the percentage of students who completed was 57.14% with 16 students completing. In cycle II the average score increased to 78.93 with a percentage increase from the pre-cycle score of 50.34% and the percentage of students who completed was 82.14% with a total of 23 students completing. Based on the results of this research, it can be concluded that the application of the SAVI assisted learning model is implementedGoogle Art and Culture can improve SBdP learning outcomes for various regional fine arts materials for class V SD Negeri 002 Loa Kulu for the 2022/2023 academic year Keyword: Learning model Somatic Auditory Visual Intellectual (SAVI), Media Google Art and Culture. SBdP Learning OutcomesAbstrak: Tujuan penelitian untuk meningkatkan hasil belajar menggunakan penerapan model pembelajaran Somatic Auditory Visual Intellectual (SAVI) berbantuan Google Art dan Culture pelajaran SBdP materi ragam seni rupa daerah kelas V SD Negeri 002 Loa Kulu tahun ajaran 2022/2023. Jenis Penelitian Tindakan Kelas (PTK) dilakukan selama dua siklus terdiri dari empat kali pertemuan. Prosedur penelitian terdiri dari empat tahap yaitu perencanaan, pelaksanaan, observasi dan refleksi. Subjek penelitian siswa kelas V berjumlah 28 dan objek penelitian adalah hasil belajar SBdP materi ragam seni rupa daerah menggunakan model pembelajaran SAVI. Teknik pengumpulan data menggunakan observasi, tes dan dokumentasi. Teknik analisis data penelitian menggunakan persentase aktivitas guru dan siswa, ketuntasan hasil belajar, rata-rata, nilai akhir dan peningkatan hasil belajar siswa. Hasil penelitian menunjukkan nilai rata-rata SBdP siswa pada pra siklus sebesar 52,5 dengan persentase siswa yang tuntas sebesar 32,14% dengan jumlah 9 siswa tuntas, kemudian pada siklus I nilai rata-rata meningkat menjadi 66,96 dengan persentase peningkatan hasil belajar sebesar 27,54% dan persentase siswa yang tuntas sebesar 57,14% dengan jumlah 16 siswa tuntas. Pada siklus II nilai rata-rata meningkat menjadi 78,93 dengan persentase peningkatan dari nilai pra siklus sebesar 50,34% dan persentase siswa yang tuntas sebesar 82,14% dengan jumlah 23 siswa tuntas. Berdasarkan hasil penelitian tersebut dapat disimpulkan penerapan model pembelajaran SAVI berbantuan Google Art dan Culture dapat meningkatkan hasil belajar SBdP materi ragam seni rupa daerah kelas V SD Negeri 002 Loa Kulu tahun ajaran 2022/2023 Kata Kunci: Model Pembelajaran Somatic Auditory Visual Intellectual (SAVI), Media Google Art dan Culture. Hasil Belajar SBdP